"BION-M" No. 1 spacecraft radiation environment as observed by the RD3-B3 radiometer-dosimeter in April–May 2013. (February 2015) - Dachev, T.P.; Tomov, B.T.; Matviichuk, Yu.N.; Dimitrov, Pl.G.; Bankov, N.G.; Shurshakov, V.V.; Ivanova, O.A.; Häder, D.-P.; Schuster, M.T.; Reitz, G.; Horneck, G.
Abstract: Space radiation has been monitored using the РД3-Б3 (in the following we use the Latin transcription RD3-B3) spectrometer–dosimeter on board a recent space flight of the Russian recoverable satellite "BION-M" No. 1. The instrument was mounted inside the satellite in a pressurized volume together with biological objects and samples. The RD3-B3 instrument is a battery operated version of the spare model of the R3D-B3 instrument developed and built for the ESA BIOPAN-6 facility on Foton M3 satellite launched on September 2007 (Häder et al., 2009 ). It is a low mass, small dimension automated device that measures solar radiation in four channels and ionizing radiation in 256 channels of a Liulin-type energy deposition spectrometer (Dachev et al., 2002 ). Cosmic ionizing radiation has been monitored and separated in 256 deposited energy spectra, which were further used for determination of the absorbed dose rate and flux. The paper summarizes the results for the Earth radiation environment at the altitude of 253–585 km. Highlights: We report observations of the space ionizing radiation at "BION-M" No. 1 spacecraft. Data are obtained by a Bulgarian build Liulin type instrument. The radiation exposure parameters are obtained at the altitude of the spacecraft.